(untitled) (Jurnal Teknologi (Sciences & Engineering), 2024)
The usage of inorganic fertilizer has been shown to have a negative impact. However, most farmers tend to use chemical fertilizers due to its significant useful effects on plants. This study aims to determine the influence of pelletized plant growth-promoting microbial consortium (PGPR) derived from fermented rice water in Pakchoy plants (Brassica rapa subsp.chinensis) growth enhancement. PGPR are characterized by tests for nitrogen fixation, phosphate solubilization and potassium solubilization, and indole compound productions which resulted all positive. The most effective isolates are chosen and was encapsulated into pellets form using bentonite powder. It was then applied to Pakchoy plants for four weeks based on four different treatments: control (T0), 0.5 g NPK fertilizer (T1), 0.1 g PGPR (T2), 0.5 g PGPR (T3) and 1.0 g PGPR (T4). The result significantly improved roots length (in cm), number of leaves and dry weight (in g). In future, the sustainable friendly approach like this can be potentially applied to the other crops like chili, rice, pineapple and vegetables.